Implementation of Good Corporate Governance and Code of Conduct at PT Bank Syariah Indonesia Tbk - Puspita, Azzahra Yuni; Tarigan, Darryl Galed Suranta; Setiawan, Fajar; Nasirwan, Nasirwan (Economic: Journal Economic and Business, 2025)
This study examines the ethical practices of accountants in the context of Islamic banking, focusing on PT Bank Syariah Indonesia Tbk (BSI). This study investigates how BSI, as a leading Islamic bank in Indonesia, implements a code of ethics in its business operations and whether BSI truly realizes its ideals as a “bank that is the pride of the people” by adhering to ethical standards. Using a qualitative approach, this study collected data through interviews, observations, and archival documents. The findings of this study highlight the importance of ethical principles in accounting, especially in Islamic banking, which emphasize fairness, transparency, accountability, and social responsibility. The implementation of Good Corporate Governance (GCG) principles at BSI, including transparency, accountability, and fairness, is critical to maintaining public trust and ensuring the integrity of financial reporting. The bank’s Code of Ethics outlines specific guidelines to prevent conflicts of interest, ensure confidentiality, and prohibit bribery, in line with Islamic principles. This study concludes that BSI’s compliance with ethical standards is critical to maintaining public trust and ensuring the integrity of financial reporting, which contributes to the development of Islamic banking in Indonesia and globally.